Le domaine, un territoire de la communauté ? - Fanny Cosandey (Les Cahiers de Framespa)
In this article, we tackle differently the relationships between individual, family and community, by resorting to texts about the Crown Estate. Indeed, these texts provide us with much information about what is really common property and its links to the community. They also allow us to understand how the Crown Estate – family property of the Capet dynasty – was part of the communal territory.